Cellular Digital Fibroma: A Comprehensive Review of a CD34-Positive Acral Lesion of the Distal Fingers and Toes - Philip R. Cohen; Robert S. Alpert; Antoanella Calame (Adis, Springer Healthcare, 2020)
Abstract Cellular digital fibroma is a benign fibrous lesion that typically occurred on either a finger or a toe. Cellular digital fibroma was introduced as a distinctive cluster of differentiation 34 (CD34)-positive lesion in July 2005. Cellular digital fibroma has been described in 20 patients: 12 men and 8 women. The patients ranged in age from 27 to 83 years old (median, 52 years old) at diagnosis. The tumor had been present from 2 months to 2 years (median, 11 months) prior to seeking medical attention. The cellular digital fibroma was usually slowly growing and asymptomatic; there has been no prior history of trauma at the tumor site. The lesion typically presented as either an erythematous or a flesh-colored, solitary papule of 5 mm or smaller. It frequently occurred on either the dorsal, lateral or ventral side of a digit. Yet, some of the lesions were located on the nail fold of the digit. Cellular digital fibroma shows a prominent cellular proliferation of spindle-shaped fibroblasts, without any atypia or mitoses, that extends from the papillary into the upper reticular dermis; diffuse and strongly positive CD34 staining is present throughout the entire tumor. There is no erosion by the tumor of the bony phalanx. Other acral tumors, such as superficial acral fibromyxoma (which also has diffuse strongly positive CD34 staining) and acquired digital fibrokeratoma (which is either CD34-negative or only focal CD34 positive), are in the clinical and pathologic differential diagnosis of cellular digital fibroma. Conservative complete excision is the treatment of cellular digital fibroma; however, even for tumors that have only been partially removed during biopsy, recurrence has not been observed. In conclusion, cellular digital fibroma is a unique CD34-positive acral lesion of the distal fingers and toes whose diagnosis requires correlation of the clinical morphology and the pathologic features of the tumor.